Target Usia Perkawinan bagi Perempuan - Shofiyulloh Shofiyulloh (Yinyang: Jurnal Studi Islam Gender dan Anak, 2019)
This study illustrates the paradigm of students at the Islamic boarding school Darussalam towards the target age of marriage. It is interesting to study when the target age is significantly analyzed in the perspective of female students. This is because, in general, marriages that occur among female students are known as arranged marriages. However, this paper explores the opinions of each female santri in determining the ideal marriage age limit for their perspective. Previously, it was reviewed in advance regarding the age regulation of maturity according to classical fiqh and the rules of legislation, in this case Law No. 1 of 1974 and compilation of Islamic Law (KHI). The final analysis is to analyze the results of a survey of about 30 female students of the Darussalam boarding school. Then proceed with classifying the age of marriage in four classifications, namely the age of marriage in an ideal level, sufficient, alert, and alert. The findings of this paper provide a clear picture that women's rights in determining the age of marriage are strongly influenced by their physical and mental maturity. Therefore, indirectly invalidated at least the age of 16 years for women regulated in the Act does not pay attention to the wishes of women themselves.